From Bohemian Lifestyle to Feminist Consciousness: Sunčana Škrinjarić and Yugoslav Women’s Writing (Knjiženstvo, journal for studies in literature, gender and culture, 2024)
This article interprets Sunčana Škrinjarić’s prose and radio plays in the context of Yugoslav cultural history as well as socialist and contemporary reflections on female authorship (its social significance as well as thematic and stylistic particularities). I reflect on Škrinjarić’s trilogy, the novels Ulica predaka [The Street of Ancestors], Ispit zrelosti [The Matriculation Exam], and Bijele strijele [The White Arrows]. In the trilogy, written between 1980 and 2004, Škrinjarić uses autobiographical material to tell the story of Tajana’s fraught coming of age and thwarted artistic ambitions. The trilogy sardonically reflects on the male-centered official and counter-cultural canon. While the trilogy is the most comprehensive example of Škrinjarić’s recurring preoccupations and character types (ambitious mediocre man, sullen young woman, struggling poet, crazed communist) and also the work in which she first introduced her polyphonic, lyrical style, I argue that she has been exploring the theme of marginality since the 1960s. In the stories “Jedno ljeto” [One Summer] and “Trovanje biljkom” [Poisoned by a Plant], the non-normative bodies were finally given a distinctly feminist slant. As her short story “Mesareva ljubav” [The Butcher’s Love] shows, even in the conservative 1990s Škrinjarić was not deterred from criticizing violence against women and the judicial system that facilitated it. The article also reflects on Škrinjarić’s lesser-known novel Kazališna kavana [The Theatre Café], a depiction of bohemia in 1950s Zagreb – the liberalism of men was pardoned, while that of women could have led to a horrific and illegal abortion. Finally, Škrinjarić’s radio play “Tamna soba” [The Dark Room], an intersectional representation of various socialist femininities, reflects pessimistically on the erasure of women’s oeuvres. These works are placed in a dialogue with scholarship on Yugoslav women writing (Lukić, Zlatar, Lóránd) as well feminist theory (Halberstam) and narratology (Cohn, Rimmon-Kenan).
Keywords: second-wave feminism; socialism; écriture feminine; creativity; agency